Pembentukan Perda Berbasis Syari’ah dalam Bingkai Negara Hukum Pancasila - Febria, Thomas; Kurniawan, Dendi (Program Magister Ilmu Hukum Universitas Ekasakti, 2025)
This research attempts to explore the validity basis (philosophical, sociological juridical, historical, and conceptual) of the formation of Sharia Regional Regulations or Regional Regulations that have a Sharia orientation, which is mostly drawn up in various regions in Indonesia. As for this research, normative juridical analyzes the problems in the formation of Sharia regulations within the framework of the Pancasila state law. Of the seven legal research approaches, the statute approach, conceptual approach, and historical approach are used to find answers to the problems posed in this study. The results of the study stated that the establishment of a Sharia-inspired Regional Regulation has a philosophical foundation in Pancasila and the 1945 Constitution, particularly Article 18, Article 18A, Article 18B, Article 25, and Article 29. Sociologically, the cultural pluralism of the Indonesian nation is always related to religion. Juridically, the provisions in Article 10 paragraph (1) letter f of Constitution Number 23 of 2014 concerning Regional Government have been amended several times, most recently by Law Number 11 of 2020 concerning Job Creation and their explanations. The provisions of Article 2 and Article 3 of Presidential Regulation Number 83 of 2015 concerning the Ministry of Religion also provide clear boundaries regarding the authority of the central and regional governments in the field of religion. This provision provides an opportunity for the regions to form regional regulations with sharia nuances. In the Jakarta Charter (Piagam Jakarta)as a historical document, the government also recognizes and legitimizes the formation of a Sharia Regional Regulation. Then based on conceptual (theoretical), the concept of asymmetric decentralization, it is possible for the Government to implement different autonomy for several regions in Indonesia which allows the development of the unique potential of each region.